Obesity, inflammation, and cancer in dogs: Review and perspectives - Marchi, Pedro H.; Vendramini, Thiago H. A.; Perini, Mariana P.; Zafalon, Rafael V. A.; Amaral, Andressa R.; Ochamotto, Vanessa A.; Da Silveira, Juliano C.; Dagli, Maria L. Z.; Brunetto, Marcio A. (Frontiers in Veterinary Science, 2022)
Obesity is the most common nutritional disease in dogs, and its prevalence has increased in recent decades. Several countries have demonstrated a prevalence of obesity in dogs similar to that ob-served in humans. Chronic low-grade inflammation is a prominent basis used to explain how obesity results in numerous negative health consequences. This is well known and understood, and recent studies have pointed to the association between obesity and predisposition to specific types of cancers and their complications. Such elucidations are important because, like obesity, the preva-lence of cancer in dogs has increased in recent decades, establishing cancer as a significant cause of death for these animals. In the same way, intensive advances in technology in the field of human and veterinary medicine (which even proposes the use of animal models) have optimized existing therapeutic methods, led to the development of innovative treatments, and shortened the time to diagnosis of cancer. Despite the great challenges, this review aims to highlight the evidence obtained to date on the association between obesity, inflammation, and cancer in dogs, and the possible pathophysiological mechanisms that link obesity and carcinogenesis. The potential to control cancer in animals using existing knowledge is also presented.